Penerapan Gessit To (Gerakan Siswa/Siswi Sehat Ma Al Falah Tolutu) Dalam Meingkatkan Pengetahuan Tentang Kesehatan Di Sekolah Ma Al Falah Tolutu - Bayu Dwisetyo; Lidia Maturbongs; Putri Diva Pakaya; Syifa F. Latoale; Bagis Pratiwi Dude; Nabila Ikram (Lembaga Pengembangan Kinerja Dosen, 2024)
Indonesian teenagers seem to be more tolerant of a lifestyle that is not good for self-care. There are many factors that influence this behavior, one of which is attitudes and knowledge about health. This knowledge and attitude can be enhanced by giving counseling or health education. The purpose of this activity is to increase the knowledge of students about adolescent health. The methods in this activity are group approaches and lectures. In addition to increasing knowledge, further dedication activities should continue to increase knowledge into improving attitudes of clean and healthy living.